Global survey on training and practice in sentinel lymph node mapping for endometrial and cervical cancer among early-career gynecologic oncologists - Tsibulak, Irina; Collins, Anna; Hsu, Heng-Cheng; Chacon, Enrique; Bizzarri, Nicolò; Baleka, Alex Mutombo; Razumova, Zoia; Theofanakis, Charalampos; Kacperczyk-Bartnik, Joanna; Strojna, Alexandra Natalia; Pletnev, Andrei; Angeles, Martina Aida; et al. (International journal of gynecological cancer, 2025)
Objective - This survey was designed to evaluate exposure to sentinel mapping for cervical and endometrial cancers in addition to the quality and availability of surgical training in sentinel procedures around the world. Furthermore, we aimed to identify obstacles in surgical training in the sentinel procedure to support the adoption of this technique in clinical practice. - Methods - A 52-item survey was developed and computed using Qualtrics XM and SurveyMonkey software. The target population were members of the European Society of Gynaecological Oncology and the International Gynecological Cancer Society aged ≤40 years. The study invitation was disseminated within both organizations’ database. The survey hyperlink was active between September and December 2022. Respondents using the same Internet Protocol address were excluded to avoid duplication of responses. Responses to <50% questions were excluded. - Results - Overall, 238 respondents joined the survey, and 182 (76.5%) provided answers that met the inclusion criteria. Sentinel mapping was implemented for a longer period and used more frequently in endometrial than in cervical carcinoma; 55% of the responders were initially trained in systematic lymph node dissection, and 22% were not yet trained in any lymph node staging. The main challenges in applying sentinel procedure for early-career gynecologic oncologists were no access to hands-on training (n = 22, 12.1%) and no clinical routine in performing systematic pelvic (n = 15, 8.2%) and para-aortic (n = 35, 19.2%) lymph node dissection in case of failed mapping. - Conclusions - Although sentinel lymph node biopsy is integrated in cervical and endometrial cancer guidelines, a significant number of institutions do not implement this procedure in clinical routine, and 22% of early-career gynecologic oncologists are not trained in any type of surgical lymph node staging. Support for sentinel mapping in national guidelines and guided training opportunities are needed to apply this method globally.